The environmental attitude of the prospective biology teachers in Indonesia - Abdulkadir Rahardjanto; H. Husamah; Samsun Hadi; Nurdiyah Lestari; Diani Fatmawati (University of Muhammadiyah Malang, 2022)
Environmental attitude should be possessed by students as an effort to manage their relationship with environmental problems. However, there has never been any study on the environmental attitudes of prospective biology teachers in Indonesia. This study aims to discover the environmental attitude of the prospective science teachers throughout Indonesia. This cross-sectional survey study analyzes the aspects of gender, grade point average (GPA), college status, and study status which are positioned as the character of the respondent whose impact on the students’ environmental attitudes are analyzed in this study. The target population size of this study is 1300 people. Thus, based on Krejcie and Morgan Table, the minimum sample size with a confidence level of 95% and margin error of 5% is 1235 students. The data collection instrument used in this study is the Environmental Attitude Inventory/EAI questionnaire which has been validated by bilingual experts and transformed into an online questionnaire by means of Google Form. SPSS software was used to examine the data. The results indicate that there is no significant difference in EA scores based on gender, GPA factor, and university status background. The difference in EA scores is affected by whether or not students have taken courses related to the environment ownership. The researchers believe that it is critical to ensure that the course materials concerning environmental education are properly planned and implemented. Courses should be supplemented with themes on environmental issues ranging from local to global scope.